Association Between Cardiometabolic Index and Blood Pressure: A Cross-Sectional Analysis of the NHANES 2015–2018 Data - Lingyan He; Ling Sun; Haihua Pan; Changlin Zhai (Reviews in Cardiovascular Medicine)
Background: Hypertension is a major risk factor for cardiovascular diseases (CVDs) and is closely related to metabolic abnormalities. The cardiometabolic index (CMI) integrates lipid profiles and anthropometric indicators, reflecting overall cardiometabolic health. However, the CMI and blood pressure (BP) relationship is poorly understood. Therefore, this study aimed to investigate the correlation between CMI and clinical BP and evaluate the potential of using this correlation as a cardiovascular risk indicator. Methods: National Health and Nutrition Examination Survey (NHANES) data from 2015 to 2018 were used to calculate the CMI based on the triglycerides to high-density lipoprotein cholesterol ratio and the waist-to-height ratio. The relationship between CMI and systolic blood pressure (SBP)/diastolic blood pressure (DBP) was analyzed using multivariate regression, threshold effect analysis, and subgroup analysis. Results: In this study cohort of 4240 participants, CMI positively correlated with SBP and DBP. After adjusting for age, gender, and race, the partial correlation for SBP was 0.56 (95% CI: 0.19–0.93; p < 0.01), while for DBP, it was 1.15 (95% CI: 0.60–1.71; p < 0.001). The threshold effect analysis revealed a positive association with SBP when the CMI was below 6.83 (β = 1.44, 95% CI: 0.64–2.24; p < 0.001) and a negative association when the CMI was above 6.83 (β = –1.52, 95% CI: –2.77– –0.28; p = 0.0123). For the DBP, a positive correlation was found when the CMI was below 2.81 (β = 1.45, 95% CI: 0.10–2.79; p = 0.0345), and a negative correlation when the CMI was above 2.81 (β = –1.92, 95% CI: –3.08– –0.77; p = 0.0012). A strong interaction was observed between the CMI and gender for the SBP (p = 0.0054) and a trend for the interaction between CMI and age for the DBP (p = 0.1667). Conclusions: This study found a significant positive correlation between the CMI and BP, with threshold effects supporting a non-linear relationship. The strong interaction between the CMI and gender for SBP suggests that the influence of the CMI on BP may be gender-dependent. These results highlight the importance of utilizing CMI in personalized cardiovascular risk stratification and underscore the relevance of considering patient factors such as gender in managing hypertension.